The Evolution of Islamic Educational Institutions in North Sumatra Indonesia - Sumanti, Solihah Titin; Nunzairina, Nunzairina; Salminawati, Salminawati (Nazhruna: Jurnal Pendidikan Islam, 2024)
This article explores the transformation of Islamic educational institutions in North Sumatra, Indonesia, focusing specifically on pesantren and madrasahs. This article used a qualitative approach that integrates historical, social, and philosophical analysis to examine changes and developments in the Islamic education system. The findings reveal that the evolution from traditional educational institutions to modern ones significantly impacts Islamic education approaches and practices, including management, learning strategies, and curriculum development tailored to contemporary educational needs. The discussion highlights the importance of pesantrens and madrasahs within Indonesia's national education framework and how these institutions adapt to the challenges of the times. The conclusion emphasizes the critical role of Islamic educational institutions in shaping and maintaining Indonesia's cultural and religious identity while providing education relevant to modern demands. This research offers insights into how Islamic educational institutions in North Sumatra endure and thrive amidst social and educational changes.